2022
DOI: 10.7324/japs.2023.45365
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of propolis activity as sucrose-dependent and sucrose-independent Streptococcus mutans inhibitors to treat dental caries using an in silico approach

Abstract: Dental caries is an oral disease that still shows high prevalence in the world. Streptococcus mutans as the main cariesrelated bacterium uses some features to exhibit its role as a cariogenic bacterium. It majorly can be classified into dependent and independent sucrose proteins. One natural source gaining interest regarding its potential to inhibit S. mutans activity is propolis. However, research has attempted to evaluate the potential inhibitor from propolis to cariesrelated protein S. mutans through an in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“… 31 Moreover, diosmetin, cosmosiin, genistin, and 3’-methoxy-5’-hydroxyisoflavone-7-O-β-D revealed as novel candidates for inhibition of Streptococcus mutans activity in caries. 29 We also found that isoetin poses strong binding interaction to AChE, Caspase3, MAPK14, NF-kB, and TNF-α that related to neuroinflammation. 49 Besides, numerous studies reported the potential antibreast cancer activity of propolis that depend on their active compounds, such as CAPE, artepillin C, and chrysin.…”
Section: Discussionmentioning
confidence: 58%
See 3 more Smart Citations
“… 31 Moreover, diosmetin, cosmosiin, genistin, and 3’-methoxy-5’-hydroxyisoflavone-7-O-β-D revealed as novel candidates for inhibition of Streptococcus mutans activity in caries. 29 We also found that isoetin poses strong binding interaction to AChE, Caspase3, MAPK14, NF-kB, and TNF-α that related to neuroinflammation. 49 Besides, numerous studies reported the potential antibreast cancer activity of propolis that depend on their active compounds, such as CAPE, artepillin C, and chrysin.…”
Section: Discussionmentioning
confidence: 58%
“…Our previous study assessed our propolis content using LC-MS/MS method. 29 We found that neobavaisoflavone, methylophiopogonone A, 3’-methoxydaidzin, and genistin as novel candidates for anti-SARS CoV-2 infection through inhibition of S2 and Mpro, 48 whereas (RR)-(+)-30-senecioylkhellactone and pinobanksin-3-O-butyrate as novel aldose reductase inhibitors in the treatment of type-2 diabetes mellitus. 31 Moreover, diosmetin, cosmosiin, genistin, and 3’-methoxy-5’-hydroxyisoflavone-7-O-β-D revealed as novel candidates for inhibition of Streptococcus mutans activity in caries.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Moreover, from 2000-2014, a total of 241 new propolis compounds in a group of flavonoids, terpenoids and phenolics were identified [ 70 ]. Our previous studies also identified numerous flavonoid and phenolic acid compounds in propolis extract [ 71-73 ]. We have also explored 658 Asian propolis compounds that are majorly in the group of flavonoids, phenolic acid, and terpenoids [ 74 ].…”
Section: Active Compounds Of Propolismentioning
confidence: 99%